1990
DOI: 10.1002/ijc.2910460525
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐1 and interleukin‐2 control granulocyte‐ and granulocyte‐macrophage colony‐stimulating factor gene expression and cell proliferation in cultured acute myeloblastic leukemia

Abstract: In vitro proliferation of leukemic cells purified from 10 cases of acute myeloblastic leukemia (AML) was analyzed in basal conditions or in the presence of exogenous recombinant (r) Interleukin (IL) I. In parallel, blasts from 5 of these patients were studied for granulocyte-macrophage colonystimulating factor (GM-CSF) or granulocyte-CSF (G-CSF) mRNA. 11-1 augmented the spontaneous AML cell proliferation in all cases and induced de novo expression or increased amounts of GM-CSF and/or G-CSF transcripts in 4 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Further, our results demonstrated that IL-1-sensitive AML patients clustered with other known myeloid growth-promoting cytokines such as GM-CSF and IL-3. While previous studies describe an effect of IL-1 predominantly on the production of GM-CSF and G-CSF by AML blasts (Bradbury et al, 1990; Cozzolino et al, 1990; Delwel et al, 1989), we show that IL-1 enhances the production of numerous other pro-inflammatory cytokines (e.g. IL-6, IL-8, MCP-1, MIP-1α, MIP-1β) from AML progenitors and blocking IL-1 signaling may mitigate these effects.…”
Section: Discussionmentioning
confidence: 96%
“…Further, our results demonstrated that IL-1-sensitive AML patients clustered with other known myeloid growth-promoting cytokines such as GM-CSF and IL-3. While previous studies describe an effect of IL-1 predominantly on the production of GM-CSF and G-CSF by AML blasts (Bradbury et al, 1990; Cozzolino et al, 1990; Delwel et al, 1989), we show that IL-1 enhances the production of numerous other pro-inflammatory cytokines (e.g. IL-6, IL-8, MCP-1, MIP-1α, MIP-1β) from AML progenitors and blocking IL-1 signaling may mitigate these effects.…”
Section: Discussionmentioning
confidence: 96%
“…Multiple studies have shown that interference with IL-1 signaling by anti-IL-1 antibodies or an IL1R1 antagonist (IL1RA) suppress proliferation of leukemic cells from a majority of AML patients (15)(16)(17)(18)(19)(20)(21)(22)(23). We therefore investigated the ability of the developed antibodies to inhibit IL-1 signaling.…”
Section: Murine Effector Cells Mediate the Therapeutic Effect In The mentioning
confidence: 99%
“…IL-1 has been demonstrated to be spontaneously produced in cultured cells of patients with AML cells. IL-1 also induces the synthesis of colony-stimulating factors (CSF) and sustains leukaemic growth (Cozzolino et al 1990;Rodriguez-Cimadevilla et d. 1990). Recent studies have revealed that the use of IL-lra on proliferate blast cells from the marrow of patients with AML inhibits their spontaneous proliferation in a dosedependent fashion.…”
Section: Acute Myeloblastic Leukaemia (Aml)mentioning
confidence: 99%